Integrated computational analysis identifies FABP4, PTGS2, and HPGD as Key molecular targets linking PET microplastic exposure to metabolic dysfunction-associated steatotic liver disease - Yi Zhang; Yao Yu; Bin Ge; Dacai Gong; Lan Zheng; Yuanyi Wang; Peng Chen (PLoS ONE, 2026)
Background Metabolic dysfunction-associated steatotic liver disease (MASLD) affects 25–38% of the global population, yet the contribution of environmental polyethylene terephthalate (PET) microplastics to its pathogenesis remains unclear. PET microplastics accumulate in the liver at approximately 4.6 particles per gram of tissue and have been implicated in metabolic disturbance, oxidative stress, and inflammation, but their molecular targets and mechanisms in MASLD are not well defined. Methods We integrated three GEO microarray cohorts (GSE37031, GSE63067, GSE89632) and performed differential expression analysis, weighted gene co-expression network analysis (WGCNA), and PET target prediction using ChEMBL, PharmMapper, and SwissTargetPrediction. Functional enrichment, protein-protein interaction network analysis, CIBERSORT-based immune deconvolution, molecular docking, and 100 ns molecular dynamics simulations were employed to identify and validate hub genes. Results Integration of MASLD transcriptomes and PET target predictions yielded 19 overlapping genes enriched in pathways related to lipid metabolism, fatty acid degradation, glycolysis/gluconeogenesis, and chemical carcinogenesis. Network topology consistently highlighted FABP4, PTGS2, and HPGD as central hub genes. Immune deconvolution revealed MASLD-associated alterations characterized by increased M2 macrophages and γδ T cells, with decreased monocytes, dendritic cells, and naive B cells. PTGS2 and FABP4 expression showed strong correlations with innate immune cells. Molecular docking demonstrated favorable PET binding to all three proteins (–6.3 to –6.9 kcal/mol), and molecular dynamics simulations confirmed stable complexes over 100 ns, with predominantly hydrophobic interactions. Conclusions Through integrated bioinformatics analysis and molecular simulation, this study identifies FABP4, PTGS2, and HPGD as potential molecular targets through which PET microplastics may influence lipid metabolism, prostaglandin signaling, and innate immune responses in MASLD. Molecular docking and dynamics simulations suggest favorable binding interactions between PET and these proteins.